(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Foreign investment is considered a basic pillar in the economy of countries and their development plans, and accordingly, the investment contract has become the most common and widespread contract, as the world witnessed a great development after the industrial revolution in the field of industry and trade, which made countries, especially developing countries, accelerate and compete in encouraging the flow of foreign capital to them ,Of course, this is related to the volume of guarantees and privileges granted by states to investors, and the most important of these guarantees is the provision of an appropriate investment climate represented by the stability in national legislation and the stability of the economic system, as the legal environment constitutes a basic guarantee for attracting investment and helps to remove investor concerns about it, especially since investment contracts are concluded between Two unequal sides, And this is done through the inclusion of contractual terms that serve as preventive conditions from disputes that may arise between the host country and the foreign investor. The most important of these conditions is the legislative stability clause, which has reached the level of legislative conditions that may be included in the body of the host country’s law after it was a contractual condition.